A Novel Continuous Glucose Monitoring System Accurately Detects Existing and Impending Hypoglycemia - CALHOUN, PETER; JOHNSON, TERRI; BALO, ANDREW; PRICE, DAVID A. (Diabetes (New York, N.Y.), 2018)
Autonomous real-time continuous glucose monitors (rtCGM), unlike intermittently scanned continuous glucose monitors (isCGM), can proactively warn users of impending hypoglycemia. This study assessed the likelihood of realized hypoglycemia when an alert is triggered in the novel factory-calibrated rtCGM system ("G6 FC" Dexcom). Subjects wearing a G6 rtCGM participated in 1 to 3 in-clinic sessions where venous YSI plasma glucose measurements were sampled every 15 minutes. Three types of hypoglycemic alerts were assessed: “Low” (<70 mg/dL), “Urgent Low” (<55 mg/dL), and the new “Urgent Low Soon” (≤55 mg/dL within 30 minutes). YSI glucose values were linearly interpolated to give estimated glucose values between YSI glucose measurements. The first “Low” and “Urgent Low” alerts were matched with actual and interpolated YSI values within ±15 minutes. The first “Urgent Low Soon” alerts were matched with actual and interpolated YSI values within 30 minutes after the alert. The Table shows 77% of “Low” alerts and 86% of “Urgent Low” alerts correctly warned of a hypoglycemic event (YSI reading below 70 mg/dL) within ±15 minutes. There were 480 “Urgent Low Soon” alerts, 86% of which correctly predicted a hypoglycemic event in the next 30 minutes. The G6 FC CGM System provides accurate alerts to patients which could facilitate actions to prevent or minimize hypoglycemia. Table.Hypoglycemic rates during a "Low" or "Urgent Low" alertType of alertNumber of alertsNumber (%) of alert events with a nadir YSI<55 mg/dL<70 mg/dL<90 mg/dLLow620185 (29.8%)478 (77.1%)596 (96.1%)Urgent Low410249 (60.7%)353 (86.1%)394 (96.1%)